Reconstruction of Antarctic climate change using ice core proxy records from the coastal Dronning Maud Land, East Antarctica - Thamban, M.; Laluraj, C.M.; Naik, S.S.; Chaturvedi, A. (Geological Society of India, 2011)
Antarctic ice core records have provided unprecedented information on past climatic changes and forcing factors on decadal to millennial timescales. The glaciochemical and stable isotope records of a shallow ice core from the coastal Dronning Maud Land (East Antarctica) were used here to reconstruct the coastal Antarctic environmental variability during the past approx. 470 years. Sea salt ion data indicate a significant additional contribution of chloride ions compared to sea water values, possibly through atmospheric scavenging. The nitrate (NO sub (3) –) profile exhibit significant temporal shifts than that of the sulphate (SO sub (4) sup (2)–), with a major shift around 1750 AD. The changes in NO sub (3) – record are synchronous with the proxy record of solar activity (sup (10) Be profile from a South Pole ice core), suggesting enhanced NO sub (3) – values during periods of reduced solar activity like the Dalton Minimum (approx. 1790-1830 AD) and Maunder Minimum (approx. 1640- 1710 AD). The delta sup (18) O records reveal that the more negative delta sup (18) O values were coeval with several events of increased NO sub (3) – concentrations, suggesting enhanced preservation of NO sub (3) – during periods of reduced air temperatures. The delta sup (18) O and delta D records of the core also suggest significant short-term and long-tem variability with more negative values indicating relatively lower air temperatures prior to 1715 AD. The delta sup (18) O records also revealed a significant warming of 2.7 Degree Celsius for the past 470 years, with a warming of approx. 0.6 Degree Celsius per century.